2007
DOI: 10.1126/science.1138140
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Provides Acquired Resistance Against Viruses in Prokaryotes

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) are a distinctive feature of the genomes of most Bacteria and Archaea and are thought to be involved in resistance to bacteriophages. We found that, after viral challenge, bacteria integrated new spacers derived from phage genomic sequences. Removal or addition of particular spacers modified the phage-resistance phenotype of the cell. Thus, CRISPR, together with associated cas genes, provided resistance against phages, and resistance specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

56
4,256
4
76

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 5,204 publications
(4,560 citation statements)
references
References 20 publications
56
4,256
4
76
Order By: Relevance
“…A relatively unexplored avenue of information storage in DNA is the ability to write information into the genome of a living cell by the addition of nucleotides over time. Using the Cas1-Cas2 integrase, the CRISPR-Cas microbial immune system stores the nucleotide content of invading viruses to confer adaptive immunity 7 . Harnessed, this system has the potential to write arbitrary information into the genome 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively unexplored avenue of information storage in DNA is the ability to write information into the genome of a living cell by the addition of nucleotides over time. Using the Cas1-Cas2 integrase, the CRISPR-Cas microbial immune system stores the nucleotide content of invading viruses to confer adaptive immunity 7 . Harnessed, this system has the potential to write arbitrary information into the genome 8 .…”
mentioning
confidence: 99%
“…In prokaryotic viral defense, the CRISPR associated (Cas) proteins, Cas1 and Cas2, function as an integrase complex to acquire nucleotides from invading viruses and store them in the CRISPR array 7,9,10 . In previous work, we found that we could direct the system to acquire synthetic sequences into the CRISPR array if those sequences are supplied as oligonucleotides 8 .…”
mentioning
confidence: 99%
“…Scientists at food company Danisco determine that the repeats are part of a bacterial defence against viruses 10 . …”
Section: March 2007mentioning
confidence: 99%
“…Their strategy included (1) the acquisition of Danisco in 2011, an agricultural/food ingredient company that made crucial progress in understanding CRISPR mechanism and the role of Cas9 [2], (2) agreements with Virginijus Siksnys from University of Vilnius, one of the founders of CRISPR technology [32,84], and (3) exclusive cross-licenses from Caribou Bioscience and ERS Genomics specific for the agricultural field. In addition, Monsanto/Bayer Crop Science recently acquired a non-exclusive license from the Broad Institute for sole use in the agricultural sector.…”
Section: Glyphosate Resistant Cropmentioning
confidence: 99%
“…1a). Once guided to the target, Cas9 catalytically cleaves the DNA sequence 3 nt upstream the 5′-NGG PAM, resulting in the activation of endogenous repair mechanisms, such as homologous recombination (HR) or non-homologous end joining (NHEJ) [2,71] (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%